Antiferroelectric Nature of CH(3)NH(3)PbI(3−x)Cl(x) Perovskite and Its Implication for Charge Separation in Perovskite Solar Cells - Sewvandi, Galhenage A. (Sci Rep, 2016)
Perovskite solar cells (PSCs) have been attracted scientific interest due to high performance. Some researchers have suggested anomalous behavior of PSCs to the polarizations due to the ion migration or ferroelectric behavior. Experimental results and theoretical calculations have suggested the possibility of ferroelectricity in organic-inorganic perovskite. However, still no studies have been concretely discarded the ferroelectric nature of perovskite absorbers in PSCs. Hysteresis of P-E (polarization-electric field) loops is an important evidence to confirm the ferroelectricity. In this study, P-E loop measurements, in-depth structural study, analyses of dielectric behavior and the phase transitions of CH(3)NH(3)PbI(3−x)Cl(x) perovskite were carried out and investigated. The results suggest that CH(3)NH(3)PbI(3−x)Cl(x) perovskite is in an antiferroelectric phase at room temperature. The antiferroelectric phase can be switched to ferroelectric phase by the poling treatment and exhibits ferroelectric-like hysteresis P-E loops and dielectric behavior around room temperature; namely, the perovskite can generate a ferroelectric polarization under PSCs operating conditions. Furthermore, we also discuss the implications of ferroelectric polarization on PSCs charge separation.